THE INFLUENCE OF HUMAN RESOURCE MANAGEMENT ON THE QUALITY OF DEVELOPMENT AND QUALITY OF SELF-POTENTIAL (A Case Study at PT. XYZ in Jakarta) - Hamdi Supriadi; Suhendar (Jurnal Ilmiah Ekonomi Manajemen & Bisnis, 2026)
This study aims to analyze the influence of Human Resource Management (HRM) on the quality of employee development and the quality of self-potential. The phenomenon underlying this research is the persistent gap between organizational investment in HR development programs and the improvement of employee potential actualization, as reflected in the employee turnover rate at PT. XYZ reaching 18% in 2025 and employee satisfaction survey results indicating that only 55% of employees felt they had adequate career development opportunities. This research employs a qualitative approach with a case study method at PT. XYZ. Data collection techniques include in-depth interviews with 12 informants consisting of HR managers, line managers, and employees with a minimum of 3 years of work experience, participatory observation, and documentation. Data analysis utilizes the interactive model of Miles, Huberman, and Saldaña, encompassing data condensation, data display, and conclusion drawing/verification. The research findings identify three main themes: (1) HRM implementation that remains administrative in nature, (2) development quality that is suboptimal due to a lack of alignment with individual needs, and (3) self-potential that has not been optimally actualized. The findings indicate that HRM practices including HR planning, training and development, performance management, reward systems, and career development have a significant influence on improving the quality of individual development and self-potential actualization. This research provides theoretical contributions in the form of developing a model of the HRM-development-self-potential relationship, as well as practical contributions in the form of strategic recommendations for strengthening HRM in organizations